Changing patterns of social services for the elderly as innovative technologies for preserving social capital - R. M. Sadykov; N. L. Bolshakova (Вестник университета)
The article examines the main problems faced by older people and suggests innovative practices and technologies of social care at home in order to preserve their social capital. Due to age and health conditions, many older people are limited in their ability to leave home and perform daily tasks and functions. Senile problems represent negative changes that affect people’s lives and are associated with poor health. The key problems of the elderly have been identified. The article notes that senior citizens need timely and long-term care to preserve their social capital, which is best provided at home and with the support of their loved ones. To implement such care, it is necessary to create long-term care centres for the elderly and the disabled. The authors of the article propose to develop services for the elderly at home, introduce innovative technologies and improve the quality of services provided. Social services play a special role in this, which is confirmed by the experience of public service centers. The introduction of innovative service practices and technologies, and the expansion of the number of social services are promising areas for preserving the social capital of the elderly.